Determinants of Internship Satisfaction among Hotel Management Students (Nepalese Journal of Hospitality and Tourism Management, 2025)
This study examines the factors influencing internship satisfaction among the students of the Bachelor of Hotel Management (BHM) in Nepal, focusing on individual factors, job characteristics, organisational environment, and contextual conditions. Findings show that students’ academic preparedness and self-motivation are fundamental to positive internship experiences. Among these, job characteristics such as task autonomy, skill variety, and feedback have the greatest impact on satisfaction. The organizational environment, including supervisor support and workplace culture, also affects satisfaction but varies depending on the internship setting. Contextual factors like location convenience and accommodation, especially for international internships, present notable challenges. The results underscore the complex nature of internship satisfaction, requiring alignment between student capabilities, well-structured job roles, supportive organizational climates, and manageable logistical arrangements. Job characteristics are identified as the most influential determinant, while contextual factors show inconsistent effects. These findings offer practical insights for curriculum developers and industry partners aiming to enhance internship experiences and better prepare hospitality students in Nepal for their professional careers.